TECHNOLOGY OF RECORDING AND PUBLICATION OF FOLKLORE SOURCES. (International Bulletin of Applied Science and Technology, 2022)
The article describes the search for folklore, the hard work of folklorists, the technology of recording epics and preparing them for publication.